Economic and social impacts of household debt traps on quality of life and solutions for agriculturists in Buriram province - Karin, Kanmanee; Klaeokla, Kanokklao (Edelweiss Applied Science and Technology, 2024)
This research aims to study the level of economic and social impacts of household debt traps on agriculturists, as well as the factors influencing their economic and social impacts on their quality of life. Additionally, it aims to study solutions to address household debt traps of agriculturists in the Sakae Phrong sub-district, Mueang district, Buriram province, using a mixed-methods approach. Data collection was divided into two phases: 1) Quantitative data analysis using a questionnaire as a research instrument with a sample group of 400 agriculturists in Sakae Phrong sub-district, Mueang district, Buriram province, employing proportional stratified random sampling and simple random sampling techniques. Statistical methods used for data analysis include frequency distribution, percentages, mean, standard deviation, and Structural Equation Modeling (SEM) analysis using the PLS-SEM method with Bootstrapping procedure for hypothesis testing. Partial Least Square (PLS) analysis was conducted using SmartPLS software, and 2) Qualitative data analysis using focus group discussion with a sample group selected by purposive sampling of 6 individuals. The research findings revealed that 1) the economic impact ( = 3.72) and social impact (= 3.78) of household debt traps are at a high level, while agriculturists' quality of life ( = 2.69) is at a moderate level., 2) The economic and social impacts of household debt traps significantly influenced on the quality of life of agriculturists (Adjusted R2 = 0.42), with direct effects on agriculturists' quality of life from the economic impacts (ß = -0.49, p < 0.001) and social impacts (ß = 0.42, p < 0.05)., and 3) It is recommended to adjust the debt structure appropriately to the potential and fairness, enhance economic capacity, and strengthen financial literacy and immunity among agricultural households.